Incorporation of Sex and Gender Guidelines Into Transplantation Literature. Issue 11 (28th September 2021) - Vinson, Amanda J.; Chong, Anita S.; Clegg, Deborah; Falk, Christine; Foster, Bethany J.; Halpin, Anne; Mannon, Roslyn B.; Oertelt-Prigione, Sabine; Palmer, Biff F.; Sapir-Pichhadze, Ruth; West, Lori J.; Wong, Germaine
Abstract : Supplemental Digital Content is available in the text.